Improving the energy efficiency of an islanded distribution network using classical and innovative computation methods. (June 2016) - Di Silvestre, M.L.; La Cascia, D.; Riva Sanseverino, E.; Zizzo, G.
Abstract: The paper presents the analysis of some potentially suitable actions for reducing the energy losses of an islanded Medium Voltage distribution network, with the aim of improving electricity distribution efficiency. For this purpose, four actions are considered: 1) increasing the network's rated voltage; 2) reactive power compensation through static capacitor banks; 3) reactive power compensation through switchable capacitor banks; 4) installation of distributed photovoltaic (PV) generation. The first two measures are typically taken into account by the distribution system operators and can be examined by means of classical design methods, whereas the latter two more innovative actions are tested here using specialized software based on the NSGA-II multi-objective optimization algorithm. The fourth action, expanding distributed PV generation, can be motivated through public or private incentives. It is investigated here using an innovative approach to the optimization problem formulation considering the perspectives of both the utility and the consumer. A case study on a small Mediterranean island real existing network is also presented. Highlights: Some actions that Utilities can implement for improving MV network efficiency are proposed. The study proposes a formulation of a multiobjective optimization problem for installing switchable capacitor banks. The study proposes an innovative formulation of the multiobjective optimization problem for installing PV units. The study puts into evidence the technical, economical and environmental beneﬁts of the proposed actions. The study puts into evidence the technical issues connected to the application of the proposed actions to a real network.